Damage detection for constituents of track-bridge systems from driving component of vehicle-rail contact response. (15th May 2022) - Yang, Y.B.; Hu, X.S.; Shi, K.; Mo, X.Q.; Zhang, B.; Wang, Z.L.; Xu, H.
Highlights: Framework for detecting damages in the constituents of rail-bridge systems from the vehicle-rail contact response. New closed-form solutions for the dual-beam system responses by a frequency domain method. IAS computed from the driving component of the contact response with high sensitivity for detecting damages. Comprehensive parametric study for relevant factors. Abstract: A theoretical framework is presented for detecting the damages in the constituents of track-bridge systems from the vehicle-rail contact response. The rail and bridge are modeled as dual beams interwoven by a viscoelastic layer to account for track fasteners, sleepers and ballast. The single-axle test vehicle is modeled as a single degree-of-freedom (DOF) system. Firstly, closed-form solutions are newly derived for the vehicle, dual beams and vehicle-rail contact response by a frequency domain method. Next, the instantaneous amplitude squared (IAS) derived from the driving component of the contact acceleration response is adopted as the damage index. The reliability of the proposed technique to detect single or multi damages of various severities in different locations of the constituents of the track-bridge system are numerically validated. Through the parametric analysis, it is confirmed that: (1) single or multi damages in the rail, interlayer and bridge can be well identified, especially for the rail; (2) the IAS computed from the driving component of the contact acceleration is baseline-free and sensitive to damages; (3) a linear relationship exists between the IAS and damage severity for the rail; (4) rail irregularity is harmful to damage detection; but tolerable for low disturbance; (5) higher vehicle speeds can be used to detect rail damages, but not for interlayer and bridge; (6) the simple supports and finite length adopted for the rail in the dual beam model are justified by comparison with the results for infinite rails; and (7) larger vehicle mass is beneficial to damage detection.